Children’s literature and educational games popularizing knowledge about the 20th century history among children at early school age - Brenk, Mikołaj (My University, 2019)
The work discusses auxiliary materials for conducting historical education of children aged 6-9 in Poland. The issue is exemplified by selected publications, which in the form of books, comic books and educational games bring about the history of Poland in the 20th century to children. Contemporary publishing positions for early school students have the advantage of teaching history in an active way – the child becomes a participant in historical events. The emotional sphere is involved, so that the acquired knowledge is memorized for a longer time and raises positive connotations. Reversing the traditional form of knowledge administration through learning from detail to the general encourages children to seek answers to emerging questions and to reach to traditional knowledge resources.
Keywords: historical education; early school education; historical comics; educational games